Extraperitoneal colostomy in laparoscopic abdominoperineal resection using a hand inserted from the perineal side. Issue 1 (January 2014) - Shiraishi, Takuya; Tomizawa, Naoki; Ando, Tatsumasa; Arakawa, Kazuhisa; Kobayashi, Katsumi; Muroya, Ken; Kurosaki, Ryo; Sato, Hiroaki; Suto, Yuji; Kato, Ryuji; Ozawa, Naoya; Sunose, Yutaka; et al.
Abstract Introduction Extraperitoneal colostomy is considered to be more effective at preventing post‐colostomy complications than intraperitoneal colostomy. However, this operation is difficult via laparoscopic surgery alone. We present an extraperitoneal colostomy technique using a hand inserted from the perineal side. Materials and Surgical Technique Extraperitoneal colostomy was performed in five patients. After the rectum was resected, a hand was inserted into the abdominal cavity from the perineal side, and pneumoperitoneum was created. The peritoneum was dissected to make the extraperitoneal route, and the proximal colon was passed along this route with fingers and laparoscopic manipulation. All procedures were completed without tissue damage or hemorrhage. No patient developed a hernia or ileus postoperatively. Discussion Laparoscopic abdominoperineal resection for an extraperitoneal colostomy is difficult via laparoscopic ports only. It can be simplified by operating with manual assistance via the perineal wound.